Pengendalian dan Pencegahan Stunting pada Keluarga Penyandang Disabilitas Melalui Program Healthy Disability Family - Rianda Dirkareshza; Diani Sadiawati; Anastasia Bernadin Dwi Mardiatmi; Laily Hanifah; Pritha Maya Savitri; Sintha Fransiske Simanungkalit; Gilang Abi Zaifa; Egi Rivaldi Gumilar; Kesya Fadhilah Azzahra; Aisyah Nurhalizah (Jurnal Pemberdayaan Masyarakat, 2024)
The problem of stunting remains a prevalent health issue in Indonesia. Stunting not only affects typically developing individuals but can also occur among persons with disabilities. The suboptimal prevention of stunting is largely due to insufficient knowledge regarding its control and prevention within the disability community. Based on this concern, the Community Service Team of UPNVJ conducted an outreach activity with the aim of educating persons with disabilities about stunting prevention. The implementation method of this activity consisted of three stages: firstly, the pre-activity phase involved preparing the necessary resources and conducting location surveys. Secondly, the execution phase included checking for stunting among participants followed by providing educational sessions on stunting prevention. Lastly, there were discussions on stunting prevention strategies and distribution of support packages to the participants. The result of this activity is that participants gain an understanding of the methods and steps for controlling and preventing stunting among individuals with disabilities, and they are able to create balanced meal patterns or portions to prevent stunting.